(untitled) (Research, Society and Development, 2019)
This paper analyzes "The rats" of Dyonélio Machado, published in 1935. The work was framed in what is conventionally called the 1930 novel. It concerns to evidence the contradictions within the bourgeois world. The assumed presupposition was that to discuss injustice and social inequality Machado forges a protagonist who does not fit into any archetype, in other words, a problematic hero, mentioned in Lukacs’ work on modern novel. Thus, the aim of the research is to generate a reflection that promotes the sense of justice and understanding of the society’s dynamics using as a motivating pillar the reading of the novel on screen. The starting hypothesis is that the problematic hero, through his unsuitable urban life, denounces capitalism. Methodologically, a bibliographic review was accomplished. In this study, it was opted for a qualitative approach based on the questions that are posed. It is worth mentioning that a literature review was done approaching the theme of the importance of social models and the social meaning of education. The research results provided tools for reflection on the understanding that education can not be neutral, as Freire’s pedagogy emphasizes. This article concluded that we can through the literature collaborate with a teaching that relates literary knowledge to social problems and class struggle.